Perempuan dan Kebijakan Publik : Urgensi RUU Tindak Pidana Kekerasan Seksual - Audra Jovani (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
After the Elimination of Sexual Violence Bill was selected as part of the House of Representatives’ Initiative Bill in the beginning of 2022, the government and people can be relieved because the Bill that was first proposed in 2016 is finally being discussed by the House of Representatives. Apart from the obstacle posed by the parties who rejected the Bill, the high number of victims served as a catalyst for the Bill to be passed. This article aims to explain the urgency of the Bill as a public policy that sides with and protects the victims of sexual violence. By reviewing various literature, the result of this article reveals that the slow discussion of the Bill was caused by differences in perspectives relating to sexual violence and the lawmakers inability to place themselves in the position of the victims, even though the Bill has to be passed in order to protect the victims, who is mostly women and children.